ANTIFUNGAL EFFICACY OF SECANG HEARTWOOD (CAESALPINIA SAPPAN L.) SOLUTIONS ON BIOFILMS OF CANDIDA ALBICANS ATCC 10231 - BRINNA LISTIANI; MEIDYAWATI, RATNA; NPA, DEWA AYU; ARNIAWATY, DWI (International Journal of Applied Pharmaceutics, 2019)
Objective: Candida albicans is a predominant fungal species found in persistent root canal infection, and its virulence depends on the ability to form biofilms. To be able to eliminate this infection, a safe irrigation solution during root canal preparation is needed. This study is conducted to investigate the antifungal properties of secang heartwood extract solutions on C. albicans biofilm. Methods: C. albicans biofilm was obtained from incubation of C. albicans ATCC 10231 at 96-well plates in 37°C for 24 h. These biofilms were exposed to various treatments: Secang heartwood in three different concentrations (25%, 33%, and 50%), sodium hypochlorite (NaOCl) 2.5%, and control group. The results of the treatment are to see the optical density (OD) value. The higher the OD values, the lower antifungal activity of the solution. Results: The mean OD result from six samples obtained the mean value of various OD values showed in ELISA reader. Antifungal efficacy of 25% secang heartwood was lower than concentration of 33% and 50%. All concentrations of secang heartwood showed higher OD values than 2.5% NaOCl but lower than control group with p=0.01. Conclusion: Secang heartwood possesses antifungal effects against C. albicans biofilm but is lower than 2.5% NaOCl. Concentration of 25% has the strongest effect against C. albicans among other concentrations. This was a preliminary study of the antifungal efficacy of secang heartwood extract solutions against C. albicans biofilm. The result indicates that this solution has the potential to be used as an herbal alternative in root canal irrigations.